Impressiveness in the realm of creation and the stories of Houshang Golshiri - قهرمان شیری (تاریخ ادبیات)
Imitation is far from the realm of Golshiri's stories. This fact must be acknowledged before anything else. Like Bahram Sadeghi, he writes with great obsession. Abbreviation is fully embodied in the writings of these two Isfahani writers, and at the same time, they are both considered as modern writers. This is the reason why today their writings are placed in the post-modern field and the two elements of form and content are indicators, despite their fame in the field of formalism, it is one of those exceptional facts that are found when analyzing their stories that make the reader wonder if form or content was more important to them.